2009
DOI: 10.1007/s00402-009-0839-3
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of nonresorbable bioactive glass–ceramic implanted into long bone defects: comparison with cancellous allografts

Abstract: The implantation of the nonresorbable glass-ceramic material into the diaphyseal defects of long bones is not suitable based on our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Four hundred and sixty-three articles were identified for the qualitative systematic review. Sixty-two articles were eligible for the quantitative systematic review [3, 6, 867]. The rest of the articles were excluded, including: 97 articles that were not in English or French [68–164], one randomized clinical trial [165], one prospective study [166], seven case series [167–173], 174 case reports [2, 174–346], 10 basic science articles [5, 347355], 26 articles that did not discuss UBC treatment [1, 356380], 17 articles that did not represent clear data on healing [381397], 18 review articles [4, 398–414], one article that was a reprint [415], three commentary articles [416–418], 36 articles with a sample size smaller than 15 [419–454], and ten articles with possibility of shared cohort [455–464] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Four hundred and sixty-three articles were identified for the qualitative systematic review. Sixty-two articles were eligible for the quantitative systematic review [3, 6, 867]. The rest of the articles were excluded, including: 97 articles that were not in English or French [68–164], one randomized clinical trial [165], one prospective study [166], seven case series [167–173], 174 case reports [2, 174–346], 10 basic science articles [5, 347355], 26 articles that did not discuss UBC treatment [1, 356380], 17 articles that did not represent clear data on healing [381397], 18 review articles [4, 398–414], one article that was a reprint [415], three commentary articles [416–418], 36 articles with a sample size smaller than 15 [419–454], and ten articles with possibility of shared cohort [455–464] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…O'Donnell et al also found that the crystalline phase of biomimetic HCA occurred rapidly in SBF as the phosphate content increased in the soda-limephosphosilicate glass system. [41] However, it is known that increasing P 2 O 5 contents in BGs increased the apatite phase in the BGCs after sintering treatment, and this would reduce the resorption rate in the BGCs [42][43][44]. Recently, some investigations has demonstrated that the bioactivity and resorption rate of β-CaSiO 3 ceramics and β-CaSiO 3 /CaB 2 O 4 BGCs were much higher than that of β-tricalcium phosphate and apatite, and these porous materials may significantly enhance the spinal fusion or calvarial defect repair in rabbit model [23,45].…”
Section: Discussionmentioning
confidence: 98%
“…An allograft bonegraft has to be both safe in use and to possess acceptable mechanical and biological properties. In an effort to overcome the limitations of autografts and allografts, a variety of synthetic bone-graft substitutes have been developed [2].…”
Section: Introductionmentioning
confidence: 99%